2016
DOI: 10.1038/srep21479
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Mapping of Lithiation Dynamics in Transition Metal Oxide Particles with Operando X-ray Absorption Spectroscopy

Abstract: Since the commercialization of lithium ion batteries (LIBs), layered transition metal oxides (LiMO2, where M = Co, Mn, Ni, or mixtures thereof) have been materials of choice for LIB cathodes. During cycling, the transition metals change their oxidation states, an effect that can be tracked by detecting energy shifts in the X-ray absorption near edge structure (XANES) spectrum. X-ray absorption spectroscopy (XAS) can therefore be used to visualize and quantify lithiation kinetics in transition metal oxide catho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…The propagation of redox reactions governs the electrochemical properties of battery materials and their critical performance metrics in practical cells [3][4][5] . The recent research progress, especially aided by advanced analytical techniques 6 , has revealed that incomplete and heterogeneous redox reactions prevail in many electrode materials, such as olivine phosphates [7][8][9][10][11][12][13][14] , layered oxides [15][16][17][18][19][20] , spinel oxides 21,22 , and conversion materials 23,24 . Advanced highcapacity cathode materials for lithium (Li) ion and sodium (Na) ion batteries are mostly polycrystalline materials that exhibit complex charge distribution (the valence state distribution of the redox-active cations) due to the presence of numerous constituting grains and grain boundaries.…”
mentioning
confidence: 99%
“…The propagation of redox reactions governs the electrochemical properties of battery materials and their critical performance metrics in practical cells [3][4][5] . The recent research progress, especially aided by advanced analytical techniques 6 , has revealed that incomplete and heterogeneous redox reactions prevail in many electrode materials, such as olivine phosphates [7][8][9][10][11][12][13][14] , layered oxides [15][16][17][18][19][20] , spinel oxides 21,22 , and conversion materials 23,24 . Advanced highcapacity cathode materials for lithium (Li) ion and sodium (Na) ion batteries are mostly polycrystalline materials that exhibit complex charge distribution (the valence state distribution of the redox-active cations) due to the presence of numerous constituting grains and grain boundaries.…”
mentioning
confidence: 99%
“…However, these studies are handicapped by the stringent sample requirements (thickness of <100 nm, for example), high-vacuum environment and the limitation in sample size. In recent years, hard X-ray full-field transition microscopy imaging combined with X-ray absorption near-edge structure (FF-TXM-XANES) was introduced as a revolutionarily new approach for visualizing electrochemically driven solid-state phase transformation18192021. The brightness and the energy tunability of synchrotron-based hard X-ray enable nanoscale spatial resolution at ∼30 nm along with high chemical and elemental sensitivities in a large field-of-view (FOV; 30 × 30 μm).…”
mentioning
confidence: 99%
“…Inhomogeneous behavior in lithium battery electrodes has been the subject of many recent articles . The presence of these heterogeneities has been revealed by both in situ and ex situ techniques, which include conventional X‐ray diffraction (XRD), energy dispersive X‐ray diffraction, X‐ray tomography, X‐ray absorption spectroscopy, transmission X‐ray microscopy, and transmission electron microscopy . Another technique, Raman spectroscopy, offers an opportunity to probe local structure in a manner that complements data obtained by the X‐ray and electron beam techniques.…”
mentioning
confidence: 99%